Space education in Malaysia universities - Mohd. Seeni, Mohd. Ibrahim; Hashim, Mazlan; Ahmad, Samsudin (2004)
In Malaysia there are 17 public universities, 18 private universities and 5 foreign university branch campuses. Space education is mainly being offered by public universuties. space education started with subjects in astronomy and related subjects under various academic programmes in Malaysia public universities such as Universiti Teknologi Malaysia (UTM), Universiti Kebangsaan Malaysia (UKM)in early 1970's and Universiti Malaya (UM) in mid 1990's. Remote Sensing programmes started in mid 1998's in UTM. Aerospace engineering programmes were offered in mid 1990's at Universiti Sains Malaysia (USM)and Universiti Teknologi Mara (UiTM). Education space law has not being given emphasis in local universities, however Universiti Malaya (UM) and UKM have initiated some steps in providing space law through related subjects in their law programmes. In this paper, space education is presented according to four areas, namely(i)Satellite technology, (ii) Space application, (iii) Space science, (iv)Space law. Some of these programmes are offered from 3-4 years, while M.Sc. programmes take 1-2 years and PhD programmes take 3-4 years.